‘Just because something works doesn’t mean it can’t be improved’: an ethnographic analysis of the health system in Black Panther’s Wakanda - Jennifer Jackson; Carla Ferreira; Samantha Perry; Carla Ginn; Melissa Scott; Elke Jaibeeh Barah; Zahra Upal; Krista Phelps; Carol Mei; Haneul Woo; Megan Tung; Farida Gadimova; et al. (BMJ Global Health)
The emergence of COVID-19 (SARS-CoV-2) has introduced significant global challenges for healthcare systems, healthcare professionals and patients. This current climate creates an opportunity to learn from equitable health systems and move toward making fundamental changes to healthcare systems. Our ethnographic analysis of Wakanda’s healthcare system in Black Panther, from the Marvel Cinematic Universe, offers opportunities for system-level transformation across healthcare settings. We propose four healthcare system themes within the context of Wakandan identity: (1) technology as an instrument (blending bodies and technology, blending technology with tradition); (2) reimagining medication; (3) warfare and rehabilitation; and (4) preventative approaches to health (prioritising collective health, deprofessionalisation of healthcare services). The preceding themes represent core elements of Wakandan health systems that allow the people of Wakanda to thrive. Wakandans retain a strong identity and cultural traditions while embracing modern technologies. We found that effective upstream approaches to health for all are embedded in anti-colonial philosophies. Wakandans embrace innovation, embedding biomedical engineering and continuous improvement into care settings. For global health systems under strain, Wakanda’s health system identifies equitable possibilities for system change, reminding us that culturally relevant prevention strategies can both decrease pressure on health services and allow all people to thrive.